Biology of Predatory Fire Caterpillar, Sycanus sp. (Hemiptera: Reduviidae), when fed Alternative with Black Soldier Fly Maggots (Hermetia illucens) - Hayati, Nadila; Rustam, Rusli; Umami, Irwin Mirza; Prasetiyowati, Andriyani (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2024)
Fire caterpillars (Sethotosea asigna, Lepidoptera: Limacodidae) are a major pest of oil palms and cause harvesting losses. Natural enemies such as Sycanus sp. are reported to control fire caterpillars. The biological of Sycanus sp. were observed in the laboratory when fed using the alternative feed, maggot Black Soldier Fly (Hermetia illucens L.). Variables observed were egg, nymph, imago stadia, and the life cycle of Sycanus sp. The data were calculated, displayed as figures and tables, and given descriptive analysis. The results showed that predatory insects, Sycanus sp., can thrive well by providing alternative feed, such as Black Soldier Fly (BSF) (Hermetia illucens) maggots. Based on the results, it was known that one female Sycanussp. Could produce 101 eggs after being fed BSF maggots, with an incubation period of 17 days. The duration of the nymph stage was around 64.16 days, with a relatively low mortality rate (2-12%). Morphologically, Sycanus sp. grew and developed well. The body length was about twice the width of the body. The age of the male was shorter than that of the female, as was the body size. The sex ratio also showed fewer males than females (2:3).